The Role of Physical Activity in the Molecular Impact of Increased Insulin-Like Growth Factor-1 (IGF-1) Levels: A Literature Review - Indra Frana Jaya KK; Legiran (Lentera Perawat, 2024)
Insulin-like growth factor-1 (IGF-1) is a key mediator of human growth hormone (HGH), which plays an important role in promoting cell growth and differentiation in childhood and continues to exert anabolic effects in adults. IGF-1 is a small peptide that circulates in serum bound to a high affinity binding protein. IGF-1 is part of a vast network of growth factors, receptors, and binding proteins involved in mediating cell proliferation, differentiation, and apoptosis IGF-I-like growth factor has broad anabolic and insulin-sensitising effects, which are generated through endocrine (in circulation) as well as paracrine/autocrine mechanisms. Serum concentrations of IGF-1 steadily increase during childhood and peak at puberty, and continue to decline since then, as does the secretion of human growth hormone. This study aims to determine the role of physical activity in molecular impact on increasing IGF-1 levels. This article is the result of a review of various research references related to the role of physical activity in molecular impact on increasing IGF-1 levels. Physical Activity in Molecular has an impact on increasing IGF-1 levels.